Functional Standartization of Rural Areas of Dolnośląskie Voivodeship - Hełdak, Maria (Bulletin of Geography. Socio-economic Series, 2010)
In the article the actual functions of rural or urban-rural communes in Dolnośląskie voivodeship (Lower Silesia) in 1996 and 2005 were indicated by applying three criteria of delimitation: structure of economy, the level of industrialisation and the level of tourism infrastructure. The research revealed that in 1996 most communes were classified as the type dominated by agriculture and at the same time they were underdeveloped with regards to tourism and were, almost totally, lacking in industry - as many as 48 out of 126 of analysed communes. In 2005 in Dolnośląskie voivodeship industrial communes prevailed which were also dominated by agriculture - altogether 47 communes in the region.